(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
The main aim to study the histopathological grading of squamous cell carcinoma tongue and to assess the risk factors of squamous cell carcinoma tongue. Histopathological grading of squamous cell carcinoma tongue is a prognostic indicator because squamous cell carcinoma tongue has potential for metastasis to lymph nodes mainly submandibular lymph node. The major risk factors are history of smoking and tobacco chewing. Surgical resection along with radiotherapy and chemotherapy is the treatment of choice. After approval from the ethical Committee both retrospective and prospective studies for 3 years duration from March 2012 to April 2015 was done and All the samples were taken from department of dentistry and department of ENT to the department of pathology for histopathological examination. All samples were processed and slides were stained with H & E and total cases in this study are 133. Squamous cell carcinoma tongue was more common in males accounting about 80.4% (107/133) with a history of smoking present 93.4 % (100/107) males and 23% (6/26) females, History of tobacco chewing seen in 91.5% (98/107) males and 34.6 % (9/26) females. History of alcohol consumption was seen in 30% (40/133) cases. On histopathological examination 71.4% (95/133) of the tumors were well differentiated, 26.3% (35/133) were moderately differentiated and 2.2% (3/133) were poorly differentiated. Most of tongue lesions were well differentiated squamous cell carcinoma, so main risk factors are smoking and tobacco chewing for commonest metastasis was to submandibular lymph node.